The effect of ankle taping on dynamic stability and active range of motion in the female athletes with and without chronic ankle instability - Tahereh Pourkhani; Ali Asghar Norasteh; Ali Shamsi; Mohammad Ali Sanjari (Physical Treatments, 2014)
Objective: The purpose of this investigation is the study of the effect of ankle taping on dynamic stability and active range of motion in the female athletes with and without chronic ankle instability. Materials & Methods: 22 female athletes participated in this investigation: 12 subjects with chronic ankle instability and 12 healthy subjects. Time to stabilization measured with force plate in the anterior-posterior (APTTS), medial-lateral (MLTTS) and vertical directions and active range of motion measured by universal goniometer before and after closed basket weave ankle taping. Paired t-test was used to evaluate the results before and after taping. A level of p≤0.05 was considered significant. Results: There were no statistically significant findings in medial-lateral, anterior-posterior and vertical TTS before and after taping in healthy group (p= 0.77, 0.33, 0.44). In injured group, there was a statistically significant finding just in vertical TTS before and after taping (p=0.001). There were statistically significant findings in range of motion of dorsiflexion, plantar flexion, inversion and eversion before and after taping in healthy group (p = 0.004, 0.000, 0.04, 0.003) and injured group (p= 0.021, 0.001, 0.001, 0.001). Conclusion: Taping can improve dynamic instability in some directions in subjects with chronic ankle instability. Keywords: Taping/dynamic stability/chronic ankle instability